Security + : - King, Todd (Pearson Education, 2003)
The Security+ certification is CompTIA's response to membership requests to develop a foundation-level certification for security workers. The IT industry is in agreement that there is a need to better train, staff, and empower those tasked with designing and implementing information security, and Security+ is an effort to meet this demand. The exam is under consideration by Microsoft as the baseline security certification for Microsoft's new security certification initiative.